Randomized study of continuous high-dose lenalidomide, sequential azacitidine and lenalidomide, or azacitidine in persons 65 years and over with newly-diagnosed acute myeloid leukemia - Medeiros, Bruno C.; McCaul, Kelly; Kambhampati, Suman; Pollyea, Daniel A.; Kumar, Rajat; Silverman, Lewis R.; Kew, Andrea; Saini, Lalit; Beach, CL; Vij, Ravi; Wang, Xiwei; Zhong, Jim; et al. (Haematologica (Roma), 2018)
Therapy of acute myeloid leukemia in older persons is associated with poor outcomes because of intolerance to intensive therapy, resistant disease and co-morbidities. This multi-center, randomized, open-label, phase II trial compared safety and efficacy of three therapeutic strategies in patients 65 years or over with newly-diagnosed acute myeloid leukemia: 1) continuous high-dose lenalidomide (n=15); 2) sequential azacitidine and lenalidomide (n=39); and 3) azacitidine only (n=34). The efficacy end point was 1-year survival. Median age was 76 years (range 66-87 years). Thirteen subjects (15%) had prior myelodysplastic syndrome and 41 (47%) had adverse cytogenetics. One-year survival was 21% [95% confidence interval (CI): 0, 43%] with high-dose lenalidomide, 44% (95%CI: 28, 60%) with sequential azacitidine and lenalidomide, and 52% (95%CI: 35, 70%) with azacitidine only. Lenalidomide at a continuous high-dose schedule was poorly-tolerated resulting in a high rate of early therapy discontinuations. Hazard of death in the first four months was greatest in subjects receiving continuous high-dose lenalidomide; hazards of death thereafter were similar. These data do not favor use of continuous high-dose lenalidomide or sequential azacitidine and lenalidomide over the conventional dose and schedule of azacitidine only in patients aged 65 years or over with newly-diagnosed acute myeloid leukemia. ( ).